Postmodern means of making short prose V. Danylenko (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article the genre and style specification of short story of V. Danilenko is analyzed through the prism of postmodernism; theme, figurative and individual copyright dominants of novelistic genre are observed, so the writer is experimenting with his genre variations and modifications within postmodern discourse.
Keywords: game; genre; irony; short fiction; novel; postmodernism; style